Reinventing revolutionary subjects in Venezuela (2012)
This article challenges orthodox Marxist conceptualisations o f the revolutionary subject by building on the autonomist Marxist feminist tradition now in its fourth decade. It argues that by expanding our conceptualization of capitalist relations to include the sphere of social reproduction, the creation of a gendered division of labour and the construction of alienated subjectivities we open a window on the multiple subjects that are at the heart of contemporary anti-capitalist struggles and render visible an increasing feminisation of resistance in Latin America. Through an analysis of the narratives of three women participants in the Urban Land Committees (CTUs) in Venezuela we see that women are at the heart of struggles to re-define the practice of politics, create new democratic subjectivities, and re-invent social transformation, processes in which woman, family and community are renegotiated and re-imagined. This analysis demonstrates the urgent need to reinvigorate a Marxist feminist praxis that can make visible, contribute to and theorise in solidarity with contemporary forms of anticapitalist struggle.